Ketaatan Abraham Dalam Perspektif Teologis: Implikasinya Bagi Kehidupan Orang Kristen - Halawa, Iman Kristina; Panggabean, Saut Maruli (Sekolah Tinggi Theologia Ebenhaezer Tanjung Enim, 2025)
This article examines Abraham's obedience in the biblical narrative, particularly in Genesis 12 and 22, from a theological perspective and its implications for the lives of Christians today. Abraham's obedience is understood not as a form of mechanical obedience, but rather as a manifestation of living faith and a response to God's call and command. Through a literature-based descriptive-analytical study, this paper shows that Abraham was willing to leave the comfort of his homeland and even sacrifice his only son as a form of total obedience to God. The study highlights how Abraham's act of faith reflects the integration of fides (faith) and obedientia (obedience), and contains theological dimensions of divine election, promise and provision. In the context of contemporary Christianity, Abraham's obedience becomes a relevant spiritual paradigm to face the challenges of faith, moral relativism, and the crisis of obedience to the divine call. This article concludes that true obedience is an act of faith that prioritises God's will, even if it demands the greatest sacrifice, and is the path to the revelation of God's providence and favour in the lives of believers.